INTEGRATED APPROACH TO INCREASE EDUCATIONAL EFFICIENCY (Ta'limning zamonaviy transformatsiyasi, 2024)
in this article, in order to improve the methodical preparation of future teachers, independent thinking, creative abilities, use of innovative pedagogical technologies, interactive methods of teaching, individual-oriented education, cooperative pedagogy, methods of working in small groups, modern information communications are widely introduced to further increase the effectiveness of educational technologies. issues of good results have been discussed.